Preparation method of optical regeneration iron-based ceramic membrane and application of optical regeneration iron-based ceramic membrane in removal of perfluorooctanoic acid
By preparing a photo-regenerated iron-based ceramic membrane that combines adsorption and photodegradation functions, the problems of efficient PFOA removal and membrane regeneration are solved, achieving efficient and economical pollutant treatment, suitable for the treatment of industrial wastewater and drinking water.
Patent Information
- Application Number
- CN202511142220.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-08-15
- Publication Date
- 2025-11-18
AI Technical Summary
Existing technologies are difficult to efficiently remove perfluorooctanoic acid (PFOA), photocatalysts are difficult to recover and have low practicality, and membrane regeneration in membrane separation technology is difficult, costly, and cumbersome to operate.
A photo-regenerated iron-based ceramic membrane was prepared, combining adsorption and photodegradation functions. This was achieved by mixing kaolinite with iron-supported zeolite molecular sieves and photodegrading PFOA under ultraviolet light. The preparation methods of the kaolinite and iron-based ceramic membrane and the preparation methods of the kaolinite and iron-supported zeolite molecular sieves were combined with adsorption and photodegradation functions to achieve efficient removal and membrane regeneration of PFOA.
It achieves efficient adsorption and photodegradation of PFOA, with a simple membrane regeneration process and a degradation rate of over 99%. The degradation process avoids the use of chemical cleaning agents, reducing costs and operational complexity, and is suitable for the treatment of industrial wastewater and drinking water.
Smart Images

Figure CN120961209A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of persistent pollutant removal, specifically to a method for preparing a photo-regenerated iron-based ceramic membrane and its application in the removal of perfluorooctanoic acid (PFOA). Background Technology
[0002] Perfluorinated compounds (PFAS) are a class of chemicals with an aliphatic carbon backbone in which hydrogen atoms are completely or partially replaced by fluorine atoms (Rahman MF, Peldszus S, Anderson W B. Behaviour and fate of perfluoroalkyl and polyfluoroalkyl substances (PFASs) in drinking water treatment: a review [J]. Water Research, 2014, 50: 318-340.). Due to their excellent physicochemical properties, PFAS are widely used in industrial production and daily life (Manojkumar Y, Pilli S, Rao PV, et al. Sources, occurrence and toxic effects of emerging per- and polyfluoroalkyl substances (PFAS) [J]. Neurotoxicology and Teratology, 2023, 97: 107-174.). In recent years, as their harmful effects on human health and ecosystems have been increasingly revealed, the level of attention given to PFAS has continued to increase. Typical PFAS, such as perfluorosulfonates (PFOS) and perfluorooctanoic acid (PFOA), have been included in the Stockholm Convention's Category 2B control list (Kim M, Son J, Park MS, et al. In vivo evaluation and comparison of developmental toxicity and teratogenicity of perfluoroalkyl compounds using Xenopus embryos[J]. Chemosphere, 2013, 93(6):1153-1160.). The carbon-fluorine (CF) bonds in the PFAS structure have high bond energies, giving PFAS chemical and thermal stability, making them difficult to degrade and defluorinate in the environment. Therefore, PFAS continuously accumulate in the atmosphere, water, and soil. Globally, from remote Arctic regions to densely populated cities, from high-altitude lakes to deep oceans, PFAS have been detected at concentrations ranging from 0.3 to 25,000 ng / L.-1 (Evich MG, Davis MJB, McCord JP, et al. Per- and polyfluoroalkyl substances in the environment[J]. Science, 2022, 375(6580):eabg9065. Xu B, Liu S, Zhou JL, et al. PFAS and their substitutes in groundwater: Occurrence, transformation and remediation[J]. Journal of Hazardous Materials, 2021, 412:125159. Wang J, Shen C, Zhang J, et al. Per- and polyfluoroalkyl substances (PFASs) in Chinese surfacewater: Temporal trends and geographical distribution[J]. Science of the Total Environment, 2024, 915:170127.). Therefore, developing new and efficient PFAS pollution control technologies has significant environmental importance and application value.
[0003] Current PFAS processing technology still has many drawbacks. Although activated carbon, ion exchange resins, and some new materials can all achieve adsorption treatment of PFAS-polluted wastewater, the adsorption process still suffers from problems such as high operating costs, poor adaptability, and the need for subsequent treatment of adsorbed PFAS (Zhang DQ, Zhang WL, Liang YN. Adsorption of perfluoroalkyl and polyfluoroalkyl substances (PFASs) from aqueous solution-A review[J]. Science of the Total Environment, 2019, 694:133606.); Advanced oxidation and advanced reduction technologies can achieve defluorination of PFAS, but they suffer from problems such as high chemical reagent costs and potential secondary pollution risks (Hori H, Nagaoka Y, Murayama M, et al. Efficient decomposition of perfluorocarboxylic acids and alternative fluorochemical surfactants in hot water[J]. Environmental Science & Technology, 2008, 42(19):7438-7443. Wang Z, Jin X, Hong R, et al. New indolederivative Heterogeneous system for the synergistic reduction and oxidation of various per- / polyfluoroalkyl substances: Insights into the degradation / defluorination mechanism [J]. Environmental Science & Technology, 2023, 57(50): 21459-21469.); Although biodegradation methods have advantages in environmental friendliness and operating cost, their degradation efficiency for key controlled pollutants such as PFOS and PFOA is limited (LiF, Su Q, Zhou Z, et al. Anaerobic biodegradation of 8:2fluorotelomer alcohol in anaerobic activated sludge: Metabolic products and pathways [J].Chemosphere, 2018, 200: 124-132. Huang S, Jaffé P R. Defluorination of perfluorooctanoic acid (PFOA) and perfluorooctane sulfonate (PFOS) by acidimicrobium sp. Strain a6[J]. Environmental Science & Technology, 2019, 53(19): 11410-11419.). Photocatalysis is considered green and promising, especially iron-based materials as photocatalysts for the degradation of PFAS, which are considered greener and more promising, based on Fe. 3+It can form complexes with PFOA, significantly enhancing the light absorption of PFOA, and promoting the degradation of PFOA under light irradiation through the ligand-metal charge transfer principle (Qian L, Georgi A, Gonzalez-Olmos R, et al. Degradation of perfluorooctanoic acid adsorbed on Fe-zeolites with molecular oxygen as oxidant under UV-A irradiation[J]. Applied Catalysis B-Environmental, 2020, 278: 119-283. Xu TY, Ji HD, Gu Y, et al. Enhanced adsorption and photocatalytic degradation of perfluorooctanoic acid in water using iron(hydr)oxides / carbonsphere composite[J]. Chemical Engineering Journal, 2020, 388: 124-230. Zhang Y, Wang X, Xu Y, et al. Photochemical degradation of perfluorooctanoic acid under UV irradiation in the presence of Fe(III)-saturated montmorillonite[J].Science of the Total Environment,2023,876:162-760.). However, photocatalysts still suffer from problems such as difficulty in recovery and low practicality. Reverse osmosis and nanofiltration technologies in physical removal strategies have been applied to PFAS removal, but membrane regeneration and fouling are the main challenges restricting the application of membrane separation technologies.Traditional membrane cleaning or regeneration often uses chemical reagent flushing methods, but these methods have disadvantages such as high cost and cumbersome operation. Long-term use of chemical cleaning agents can also lead to a decline in membrane performance (Jhaveri JH, Murthy ZV PA comprehensive review on anti-fouling nanocomposite membranes for pressure driven membrane separation processes[J].Desalination,2016,379:137-154. Asif MB, Zhang Z.Ceramic membrane technologyfor water and wastewater treatment:A critical review of performance,full-scale applications,membrane fouling and prospects[J].Chemical EngineeringJournal,2021,418:129481.). Summary of the Invention
[0004] Objective of the Invention: To address the problems existing in the prior art, this invention provides a method for preparing a photo-regenerated iron-based ceramic membrane. This iron-based ceramic membrane exhibits both high-efficiency adsorption and photodegradation functions for PFOA, and the pollutant degradation process is also the membrane regeneration process. Furthermore, this invention provides an application pathway of "high-efficiency enrichment in water - non-aqueous phase PFOA photodegradation and membrane regeneration," coupling adsorption enrichment, photocatalytic degradation, and membrane regeneration processes, effectively solving the problems of difficult photocatalyst recovery, low practicality, and the difficulty of membrane regeneration in current membrane separation technologies.
[0005] The present invention also provides the application of the photo-regenerated iron-based ceramic membrane in the removal of PFOA.
[0006] Technical solution: To achieve the above objectives, the present invention provides a method for preparing a photo-regenerated iron-based ceramic film, comprising the following steps:
[0007] (1) Grind the kaolinite and iron zeolite molecular sieve thoroughly to make them evenly mixed, and then add the binder and dispersion medium and continue grinding;
[0008] (2) The mixture obtained in step (1) is dried at room temperature, and the dried powder is pressed into shape.
[0009] (3) The material pressed in step (2) is sintered at high temperature, and the final iron-based ceramic film is obtained after sintering.
[0010] In step (1), the mass ratio of kaolinite to iron zeolite molecular sieve is 1:1 to 1:1.2, the binder is a polyvinyl alcohol solution with a concentration of 5±0.5wt%, and the mass of the added polyvinyl alcohol solution is 10±1wt% of the sum of the masses of kaolinite and iron zeolite molecular sieve.
[0011] In step (1), the dispersion medium is ethanol, methanol or isopropanol.
[0012] In step (2), a hydraulic press is used for pressing and forming. The pressure of the hydraulic press is 150-200 MPa, and the pressure holding time is 1-2 minutes.
[0013] In step (3), the high-temperature sintering temperature is 900–1000℃, and the heating rate is 5–10℃ / min. -1 Sintering time: 2-2.5 hours.
[0014] The photo-regenerated iron-based ceramic membrane prepared by the method described in this invention.
[0015] The application of the photo-regenerated iron-based ceramic membrane described in this invention in the removal of PFOA.
[0016] The iron-based ceramic membrane is used in the filtration and removal of low concentrations of PFOA from water.
[0017] In this process, an iron-based ceramic membrane is fixed in a replaceable membrane filter and mounted on a syringe. Then, pressure is applied using the syringe to slowly filter the PFOA solution through the iron-based ceramic membrane.
[0018] Furthermore, the application process is as follows: the iron-based ceramic membrane is fixed in a replaceable membrane filter and installed on a 5mL syringe, and then pressure is applied by the syringe to slowly filter the PFOA solution through the iron-based ceramic membrane.
[0019] Preferably, the concentration of the PFOA solution is 100 ± 5 μg / L. -1 The pH value is 7.0±0.1.
[0020] The application of the photo-regenerated iron-based ceramic membrane described in this invention in the photodegradation of perfluorooctanoic acid.
[0021] Among these methods, the iron-based ceramic film loaded with PFOA was irradiated with ultraviolet light or white light, with a light power density of 35–40 mW / cm². -2 The reaction temperature is controlled at 25-30℃ for 12-24 hours.
[0022] Preferably, the present invention also provides the application of iron-based ceramic films in the ultraviolet light degradation of perfluorooctanoic acid.
[0023] Furthermore, the application process is as follows: the iron-based ceramic membrane loaded with PFOA is placed in a non-aqueous phase photoreactor for ultraviolet irradiation. During the experiment, the relative humidity is controlled by adjusting the flow meters at the front end of the two channels, and the concentration of PFOA is 3.5 ± 0.1 mg g. -1 .
[0024] Preferably, the iron-based ceramic film loaded with PFOA is irradiated with ultraviolet light using a 500W high-pressure mercury lamp, with a light power density of 35–40 mW / cm². -2 .
[0025] Preferably, the mixed gas flow rate is maintained at 0.4 L / min. -1 Before exposure to light, place the iron-based ceramic membrane inside the quartz reactor chamber and continuously ventilate for more than 30 minutes to stabilize the humidity.
[0026] Preferably, to ensure uniform illumination, the iron-based ceramic film sample is rotated 180° at the midpoint of each experimental time period.
[0027] This invention involves thoroughly grinding kaolinite and iron-supported zeolite molecular sieves (Fe-zeolite), then adding a polyvinyl alcohol solution as a binder and continuing grinding. The resulting mixture is dried, powdered, and then pressed into shape using a hydraulic press and sintered in a muffle furnace to obtain an iron-based ceramic membrane. This iron-based ceramic membrane can achieve highly efficient filtration and removal of low concentrations of perfluorinated compounds in water. The perfluorinated iron-based ceramic membrane can achieve highly efficient degradation and defluorination of perfluorinated compounds and membrane regeneration under non-aqueous conditions through ultraviolet light irradiation. This invention couples adsorption enrichment, photocatalytic degradation, and membrane regeneration processes in this ceramic membrane, integrating the advantages of membrane separation technology and photocatalysis technology, demonstrating promising application prospects.
[0028] The core mechanism in this invention is the unique Fe on Fe-zeolite. 3+ The active site can adsorb PFOA by forming an inner-layer complex with PFOA, while the inner-layer complex [PFOA-Fe]... 2+ The formation of C7F can reduce 15 COO - Transformed into C7F 15 The activation energy of COO· under light irradiation causes PFOA to degrade via the LMCT (ligand-to-metal charge transfer) process, in which ferric iron is reduced to ferrous iron, C7F. 15 COO- is converted to C7F. 15 COO·. Divalent iron is re-oxidized to trivalent iron by the generated hydroxyl radicals or oxygen to achieve membrane regeneration.
[0029] This invention is the first to design and develop a photo-regenerating iron-based ceramic membrane with adsorption and photodegradation functions specifically for PFOA. It also proposes for the first time an application path for PFOA: "highly efficient enrichment in water → photodegradation of PFOA in non-aqueous phase and membrane regeneration." This invention prepares an iron-based ceramic membrane from iron-based artificial minerals, coupling adsorption enrichment, photocatalytic degradation, and membrane regeneration processes, integrating the advantages of membrane separation and photocatalysis technologies. Photocatalysis is a green and efficient method for PFOA degradation and defluorination; however, current powdered catalysts require centrifugation or filtration for recovery in actual wastewater applications, which is not conducive to large-scale engineering applications. Applying membrane modules to water treatment solves this problem. Furthermore, traditional membrane separation is a physical process; while it can achieve efficient pollutant enrichment through surface retention, it cannot achieve pollutant mineralization. Membrane cleaning or regeneration also increases costs. The iron-based ceramic membrane prepared in this invention can degrade pollutants through ultraviolet light, and the pollutant degradation process is also a membrane regeneration process. Furthermore, the treatment method proposed in this invention, which involves enriching the PFOA first and then photodegrading it under non-aqueous conditions, is also an exploration of PFOA degradation technology under non-aqueous conditions. It also has the potential to utilize natural light to degrade PFOA, which is of great significance from both an engineering and economic perspective.
[0030] Beneficial effects: Compared with the prior art, the present invention has the following advantages:
[0031] This invention utilizes a specific method to prepare an iron-based ceramic membrane from iron-based zeolite molecular sieves, achieving integrated high-efficiency adsorption and photoinduced regeneration of PFOA. This ceramic membrane is effective for low concentrations of PFOA (100 μg / L). -1 A single membrane filtration process can achieve a removal rate of over 99%; after adsorption saturation, the iron-based ceramic membrane can degrade 73% of PFOA by irradiation with ultraviolet light for 12 hours, while photo-oxidation reduces Fe on the membrane surface. 3+ The recycling process regenerates the ceramic membrane, avoiding secondary pollution and membrane structure damage caused by the use of chemical cleaning agents.
[0032] The iron-based ceramic membrane prepared by this invention maintains a high degradation rate of PFOA under various humidity conditions and exhibits good reusability, remaining stable even after five cycles. The unique "aqueous phase enrichment-non-aqueous phase photoregeneration" pathway avoids the engineering complexities of adding a light source to water, while pollutant enrichment significantly improves light energy utilization efficiency and provides application possibilities for outdoor natural light degradation. This method is simple to operate, low in cost, and applicable to various scenarios such as industrial wastewater and drinking water, providing a highly efficient, economical, and sustainable solution for PFOA pollution control. Attached Figure Description
[0033] Figure 1 This is a schematic diagram of the replaceable membrane filter used in this invention;
[0034] Figure 2 This is a schematic diagram of the photoreaction device used in this invention;
[0035] Figure 3 XRD patterns of iron zeolite molecular sieve, unsintered iron-based ceramic membrane, and sintered iron-based ceramic membrane;
[0036] Figure 4 (a) is a pore size distribution diagram of the iron-based ceramic membrane, and (b) is a water contact angle diagram of the iron-based ceramic membrane.
[0037] Figure 5 Comparison of PFOA adsorption effects on iron zeolite molecular sieves and kaolinite;
[0038] Figure 6 The graph shows the filtration and removal performance of iron-based ceramic membranes for PFOA.
[0039] Figure 7 (a) is a graph showing the photodegradation of PFOA by iron-based ceramic membrane and kaolinite ceramic membrane in air atmosphere with a relative humidity of 50%. (b) is a graph showing the change in the concentration of fluoride ions generated by the photodegradation of PFOA by iron-based ceramic membrane over time.
[0040] Figure 8 Chromatograms (a, c) and mass spectra (b, d) of the products detected after 12 h in the UV / FCM / PFOA non-aqueous system, and chromatograms (e, g, i) and mass spectra (f, h, j) of the products detected after 12 h in the UV / FCM (immersed in aqueous solution) / PFOA system.
[0041] Figure 9 (a) is a graph showing the degradation efficiency of iron-based ceramic membranes against PFOA under different humidity (10%-90%) and air atmospheres, and (b) is a graph showing the degradation efficiency of PFOA against nitrogen, air and oxygen atmospheres under 50% relative humidity.
[0042] Figure 10 The experimental results of loading and degradation of PFOA on an iron-based ceramic membrane for five cycles are shown in the figure.
[0043] Figure 11 The image shows a comparison of the photodegradation effect of iron-based ceramic films on PFOA under ultraviolet light and simulated natural light conditions. The experimental conditions were in air atmosphere with a relative humidity of 50%.
[0044] Figure 12 A schematic diagram illustrating the mechanism of PFOA removal and photodegradation of PFOA through iron-based ceramic membrane filtration to achieve membrane regeneration. Detailed Implementation
[0045] The technical solution of the present invention will be further described below with reference to the accompanying drawings.
[0046] In the following embodiments, the iron zeolite molecular sieve used is a beta-type zeolite molecular sieve, purchased from Zhuoran Environmental Protection Technology (Dalian) Co., Ltd., and the kaolinite is purchased from the Clay Mineralogical Society Standard Clay Resource Library (Purdue University, Indiana, USA).
[0047] PP replaceable membrane filter ( Figure 1 Purchased from Delu New Material Technology Co., Ltd., model number DL-PP-FH, specifically a 13mm PP replaceable membrane filter.
[0048] The photocatalytic reaction device is a conventional photocatalytic reaction device. Figure 2 The experiment begins with a high-pressure gas cylinder. One gas stream flows into a washing bottle containing ultrapure water, carrying water vapor to form a humid gas stream. The other stream flows into a washing bottle containing phosphorus pentoxide, becoming a dry gas stream. During the experiment, the relative humidity is controlled by adjusting the flow meters at the front end of the two streams, and the mixed gas flow rate is maintained at 0.4 L / min. -1 Dry and wet gases are mixed inside a sealed quartz reaction vessel. During the experiment, the relative humidity is controlled by adjusting the flow meters at the front end of the two channels, and the humidity is monitored in real time by a humidity probe at the end of the channels. A 500W mercury lamp light source is located directly above the quartz reaction vessel. The quartz reaction vessel has a jacket, and a constant temperature water bath maintains a stable reaction temperature inside the quartz reaction vessel through a circulating water system.
[0049] Example 1
[0050] A method for preparing a photo-regenerated iron-based ceramic film, comprising the following specific steps:
[0051] (1) Use a mortar and pestle to grind kaolinite and iron zeolite molecular sieve in a mass ratio of 1:1 until they are mixed evenly. Then add 10wt% polyvinyl alcohol (type 1788) solution (the mass fraction of polyvinyl alcohol in the solution is 5wt%) as a binder and continue grinding evenly with ethanol as the dispersion medium. The amount of ethanol should be enough to submerge the solid powder.
[0052] (2) The mixture obtained in step (1) was dried at room temperature for 12 hours. 0.12 g of the dried powder was weighed and pressed into shape using a hydraulic press under a pressure of 200 MPa for 1 minute.
[0053] (3) The pressed discs from step (2) are placed in a muffle furnace and heated at a rate of 5°C / min. -1 The iron-based ceramic film was sintered at 900℃ for 2 hours. After sintering, the final iron-based ceramic film was obtained with a mass of 0.10g ± 0.01g.
[0054] As a comparative study, a kaolinite ceramic membrane without the addition of iron zeolite molecular sieve (i.e., the mass of kaolinite in the kaolinite ceramic membrane is equal to the total mass of kaolinite and iron zeolite molecular sieve in the iron-based ceramic membrane) was prepared according to the same preparation method.
[0055] At the same time, without the addition of clay minerals such as kaolinite, it is difficult to form ceramic films using a hydraulic press.
[0056] Example 2
[0057] The stability of the active raw material iron zeolite molecular sieve in the iron-based ceramic membrane prepared in Example 1 was investigated using X-ray diffraction. The specific steps were as follows:
[0058] (1) Weigh a small amount of powder made from iron-based ceramic membranes before and after sintering and iron zeolite molecular sieve respectively, and place the sample on the sample stage of the X-ray diffractometer to press the sample.
[0059] (2) The crystal structures of the three samples in (1) were characterized using X-ray diffraction. Cu-Kα was used as the radiation source (λ = 0.154178 nm), and the scanning speed was 1°s. -1 The scanning range is 10-40° (2θ). The test results are as follows: Figure 3 As shown.
[0060] XRD patterns showed that the characteristic diffraction peak (12.4°) corresponding to the kaolinite (001) crystal plane disappeared after sintering, indicating that the high-temperature calcination caused the collapse of the kaolinite crystal structure. However, the characteristic peak (22.5°) corresponding to the iron zeolite molecular sieve (302) crystal plane remained, indicating that the crystal structure of the iron zeolite molecular sieve remained intact during sintering. This structurally stable iron zeolite preserved the adsorption and catalytic degradation activity of PFOA for the ceramic membrane.
[0061] Example 3
[0062] The surface properties of the iron-based ceramic film prepared in Example 1 were examined, and the specific steps were as follows:
[0063] (1) Using an automatic mercury porosimeter, the average pore size and porosity of the iron-based ceramic membrane were measured. The test results are as follows: Figure 4 a;
[0064] (2) The water contact angle of the iron-based ceramic membrane was analyzed using a water contact angle analyzer. The iron-based ceramic membrane was placed on the sample stage, and deionized water droplets were dropped onto the surface for testing. The test results are as follows: Figure 4 b.
[0065] Porosity analysis using mercury intrusion porosimetry revealed a uniform pore size distribution (average 57.93 nm) and high porosity (39.77%) on the membrane surface. The ultra-low water contact angle (13.9°) demonstrates the excellent hydrophilicity of the iron-based ceramic membrane, suggesting that it will possess strong capillary forces and high flux characteristics.
[0066] Example 4
[0067] The adsorption effect of iron zeolite molecular sieve, the active raw material in iron-based ceramic membranes, on PFOA was investigated. The specific steps were as follows:
[0068] (1) First, add 0.1g of iron zeolite molecular sieve to a 250mL capped glass bottle, and prepare a solution with a concentration of 20mg / L using ultrapure water (conductivity 18.2MΩcm). -1 Prepare a PFOA solution, and add 100 mL to a glass bottle, then use 0.1 mol L... -1 The pH of the reaction solution was adjusted to 7 ± 0.1 using NaOH / HClO4. Finally, the glass bottle was placed in a constant-temperature shaker, and the shaker speed was adjusted to 150 rpm. -1 The temperature was kept constant at 25±1℃. The control group had the iron zeolite molecular sieve replaced with kaolinite of the same concentration.
[0069] (2) Take 1 mL of sample at 0, 2, 5, 10, 20, 30, 60 and 120 min of oscillation adsorption time. Filter the sample through a 0.22 μm polypropylene (PP) filter membrane before testing.
[0070] (3) The PFOA content in the sample was measured using high performance liquid chromatography (HPLC). The specific results are as follows: Figure 5 As shown.
[0071] Iron zeolite molecular sieves can completely adsorb 20 mg L within approximately 20 minutes. -1 The PFOA adsorption performance of kaolinite is significantly better than that of kaolinite, which has almost no PFOA adsorption capacity.
[0072] Example 5
[0073] The specific steps for investigating the filtration and removal efficiency of iron-based ceramic membranes for PFOA are as follows:
[0074] (1) Fix the iron-based ceramic film prepared in Example 1 onto... Figure 1 The PP replaceable membrane filter shown is installed in a 5mL syringe;
[0075] (2) Using a syringe to apply pressure, dispense 5 mL of PFOA solution (concentration 100 μg / L). -1 (pH 7.0±0.1) was slowly filtered through an iron-based ceramic membrane, and the filtrate was collected and filtered through a 0.22μm PP membrane for subsequent analysis;
[0076] (3) The low concentration of PFOA in the filtration experiment was measured using ultra-high performance liquid chromatography-mass spectrometry (UPLC-MS / MS). The specific results are as follows: Figure 6 As shown.
[0077] Iron-based ceramic membranes can filter materials with an initial concentration of 100 μg / L in a single pass.-1 The removal rate of PFOA is approximately 99%.
[0078] Example 6
[0079] The main focus was on the photocatalytic degradation and defluorination effect of the iron-based ceramic membrane prepared in Example 1 on POFA. The specific steps were as follows:
[0080] (1) Before the photo-reaction, 3.5 mg g of iron-based ceramic film was loaded onto it. -1 The specific procedure for preparing PFOA is as follows: Prepare a solution with a concentration of 10g / L. -1 A methanol solution of PFOA was prepared, and 35 μL of this solution was added dropwise onto the iron-based ceramic membrane prepared in Example 1. After the methanol completely evaporated, PFOA was successfully loaded onto the ceramic membrane. The iron-based ceramic membrane was then placed in a... Figure 2 In the photoreactor apparatus shown, the rightmost part of the apparatus is a high-pressure gas cylinder. One gas path is introduced into a gas washing bottle containing ultrapure water, carrying water vapor to form a humid gas flow. The other path is introduced into a gas washing bottle containing phosphorus pentoxide, becoming a dry gas flow. During the experiment, the relative humidity is controlled to 50% by adjusting the flow meters at the front end of both paths, and the mixed gas flow rate is maintained at 0.4 L / min. -1 Dry and wet gases are mixed in a sealed quartz reaction vessel, with humidity monitored in real time by a humidity probe at the end of the passage. A 500W mercury lamp light source is located directly above the vessel. The quartz reaction vessel has a jacket, and a constant-temperature water bath maintains a stable reaction temperature (25℃) within the vessel through a circulating water system. Before light exposure, an iron-based ceramic membrane is placed inside the quartz reaction vessel chamber, and continuous ventilation is maintained for at least 30 minutes to stabilize the humidity.
[0081] (2) A 500W mercury lamp was used as the light source, with a light power density of 40mW / cm². -1 The reaction temperature was controlled at 25±1℃. To ensure uniform illumination, the iron-based ceramic film sample was rotated 180° at the midpoint of each experimental time period.
[0082] The control group replaced the iron-based ceramic membrane with the kaolinite ceramic membrane prepared in Example 1 without the addition of iron zeolite molecular sieve;
[0083] (3) During the photodegradation process, iron-based ceramic membrane samples were collected at specific time points (0, 0.5, 1, 2, 4, 6, 9, 12 h) for further analysis. A 10 mL mixture of water (pH 2.0) and acetonitrile (1:1 volume ratio) was used as the PFOA extraction solution, and the mixture was shaken at 150 rpm in a constant temperature shaker. -1 Shake continuously for 10 hours, using 10 mL of ultrapure water with a pH of 12 as F. - The extract was heated in a constant-temperature shaker at 150 rpm. -1 The rotation speed was oscillated for 1 hour to ensure that the adsorbed PFOA and F- Completely extracted from the iron-based ceramic membrane. After extraction, filtered through a 0.22 μm PP filter membrane before analysis, where F... - The sample to be tested requires 0.1 mol / L. -1 The pH of the solution was adjusted to 7.0 ± 0.1 using NaOH and HClO4. The contents of PFOA and inorganic fluoride ions in the sample were measured using HPLC and a fluoride ion-selective electrode, respectively. Specific results are shown below. Figure 7 As shown.
[0084] Figure 7 The results showed that the iron-based ceramic membrane achieved a 73% degradation rate of loaded PFOA after 12 hours of UV irradiation, while the kaolinite ceramic membrane only degraded 11%, confirming that the iron zeolite molecular sieve plays a crucial role in the PFOA degradation process. However, the detection revealed that the F- concentration did not continuously increase with the progress of the reaction. Figure 7 b) It is speculated that the lost F- may have evaporated in the form of HF.
[0085] Example 7
[0086] The intermediate products of PFOA photocatalytic degradation by iron-based ceramic membranes were investigated, and the specific steps were as follows:
[0087] (1) The photocatalytic degradation experiment of PFOA by iron-based ceramic membrane was carried out according to the method of steps (1) and (2) in Example 6. After 12 hours of reaction, the iron-based ceramic membrane sample was collected. The adsorbed PFOA was completely extracted from the iron-based ceramic membrane using the extraction method in Example 6 (3). After extraction, the sample was filtered with a 0.22 μm PP filter membrane and then tested.
[0088] (2) To comprehensively investigate the intermediate products of PFOA photocatalytic degradation using iron-based ceramic membranes and eliminate the influence of product volatilization, the intermediate products of PFOA photocatalytic degradation using iron-based ceramic membranes immersed in water were also investigated. Other steps were the same as step (1) in Example 4. The intermediate products were identified using a high-performance liquid chromatography-quadrupole time-of-flight mass spectrometry (HPLC-QTOF-MS) system. The results are as follows: Figure 8 As shown;
[0089] Two short-chain perfluorocarboxylic acids (PFCAs) were identified by HPLC-QTOF-MS analysis of the reaction intermediates under non-aqueous conditions. Figure 8Although no PFOA degradation intermediates reported in other literature were detected, this does not mean they were not formed. Previous studies have indicated that short-chain PFCAs and fluorinated polyols are typical intermediates of PFOA conversion, and they exhibit higher volatility compared to long-chain products (especially under non-aqueous conditions). To more comprehensively analyze PFOA conversion products, further analysis was conducted on possible degradation products in aqueous solution, and several short-chain PFCAs, including PFPeA, PFHxA, and PFHpA, were detected. Figure 8 ej). The number of products detected under non-aqueous conditions was small and the concentration was low. However, this experiment proves that the ceramic membrane prepared in this invention is not ineffective in degrading PFOA, but rather that the intermediate products generated under non-aqueous conditions are easily volatilized.
[0090] Example 8
[0091] The effects of reaction atmosphere and humidity on the photodegradation of PFOA were investigated, and the specific steps were as follows:
[0092] (1) Load 3.5 mg g onto the iron-based ceramic membrane according to the method in Example 6(1). -1 PFOA, and place the iron-based ceramic membrane in such Figure 2 In the photoreactor apparatus shown, gases (air, nitrogen, and oxygen) were introduced during the experiment. The relative humidity was controlled to be 10%, 50%, and 90% by adjusting the airflow ratio between the two gas washing bottles (one gas inlet contained ultrapure water, and the other gas washing bottle contained phosphorus pentoxide). The flow rate of the mixed gas was maintained at 0.4 L / min. -1 Before each light exposure experiment, the iron-based ceramic membrane was placed in the quartz reactor chamber and continuously ventilated for more than 30 minutes to stabilize the humidity.
[0093] (2) A 500W mercury lamp was used as the light source, with a light power density of 40mW / cm². -1 The reaction temperature was controlled at 25±1℃. To ensure uniform illumination, the iron-based ceramic film sample was rotated 180° at the midpoint of each experimental time period.
[0094] (3) During the photodegradation process, iron-based ceramic membrane samples were collected at specific time points (0, 0.5, 1, 2, 4, 6, 9, 12 h) for further analysis. The adsorbed PFOA was completely extracted from the iron-based ceramic membrane using the extraction method in Example 6(3). After extraction, the samples were filtered through a 0.22 μm PP filter membrane. The PFOA content in the samples was measured using HPLC, and the specific results are as follows: Figure 9 As shown.
[0095] like Figure 9As shown, humidity (10%–90%) has a negligible effect on PFOA degradation efficiency, indicating that the iron-based ceramic membrane can efficiently degrade PFOA over a wide humidity range. Introducing N2 inhibits the degradation process, while O2 promotes it, as it may regulate the generation of reactive oxygen species. In summary, the non-aqueous phase system is only slightly inhibited under anoxic conditions, but it can effectively degrade PFOA under different humidity conditions, suggesting that it can maintain high degradation efficiency under real-world environmental conditions.
[0096] Example 9
[0097] The specific steps for investigating the stability and reusability of iron-based ceramic membranes are as follows:
[0098] (1) The iron-based ceramic membrane (0.1 g) prepared in Example 1 was placed in a container containing 10 mL of a solution with a concentration of 40 mg L -1 The PFOA solution (pH adjusted to 7.0 ± 0.1) was placed in a glass vial. The vial was then placed in a constant-temperature shaker (25 ± 1 °C) at 150 rpm for [time missing]. -1 The solution was shaken at a constant speed for 1 hour. After adsorption saturation, 1 mL of the solution was filtered through a 0.22 μm PP filter membrane for analysis. The PFOA content in the sample was measured using HPLC to calculate the PFOA loading.
[0099] (2) Place the iron-based ceramic membrane, which has been saturated with adsorption in step (1), in a place such as Figure 2 In the photoreactor shown, the degradation experiment was conducted in an air atmosphere with a relative humidity of 50% (according to the method in step (2) of Example 6), and subjected to ultraviolet light irradiation for 12 hours. A 500W mercury lamp was used as the light source, with a light power density of 40mW / cm². -1 The reaction temperature was controlled at 25±1℃. The adsorbed PFOA was completely extracted from the iron-based ceramic membrane using the extraction method in Example 6(3). After extraction, the sample was filtered using a 0.22μm PP filter membrane. The PFOA content in the sample was measured by HPLC to calculate the degradation rate of PFOA.
[0100] (3) Perform 5 cycles according to steps (1) and (2), and the experimental results are as follows. Figure 10 As shown.
[0101] After 5 cycles, the loading and degradation rate of PFOA decreased slightly, possibly due to the dissolution of iron ions leading to a reduction in active sites. However, the loading and degradation rate remained at approximately 80% of the initial efficiency after 5 cycles, highlighting its practical reuse potential and providing an important guarantee for its practical engineering applications.
[0102] Example 10
[0103] The effect of iron-based ceramic membranes on PFOA degradation under simulated natural light conditions was investigated. The specific steps were as follows: a 500W xenon lamp was used as the light source, and the light power density was 40mW / cm². -1 Other conditions were the same as in steps (1) and (2) of Example 6. Iron-based ceramic membrane samples were collected at specific time points (0, 0.5, 1, 2, 4, 6, 9, 12 h) for further analysis. PFOA adsorbed using the extraction method in Example 6 (3) was completely extracted from the iron-based ceramic membrane. After extraction, the samples were filtered through a 0.22 μm PP filter membrane before analysis. The PFOA content in the samples was measured using HPLC, and the experimental results are as follows. Figure 11 As shown.
[0104] The results show that although the conversion rate of PFOA on the surface of the iron-based ceramic membrane is slower under simulated natural light irradiation than under mercury lamp irradiation, it still maintains effective degradation efficiency. This indicates that direct natural light irradiation can also achieve the decomposition of PFOA and the regeneration of the iron-based ceramic membrane material. This finding further confirms the broad application prospects of the "iron-based ceramic membrane enrichment-photochemical regeneration" coupled technology in the treatment of perfluorinated compound-contaminated water bodies, highlighting the operability advantages of this technology in practical environmental remediation projects.
[0105] Based on the above experimental analysis, the inventive principle of this invention can be summarized as follows: Figure 12 As shown: During filtration, PFOA reacts with Fe on the iron-based ceramic membrane. 3+ Complexation to form [PFOA-Fe ]2+ The complexed PFOA is adsorbed. Under UV excitation, the complexed PFOA is further oxidized (C7F) via a ligand-metal charge transfer process. 15 · C7F 15 • Combines with dissolved oxygen or ·OH to form C7F 15 OO·or C7F 15 OH. C7F 15 OO· can be converted into C7F through a series of free radical reactions. 15 OH. The generated C7F 15 OH will be further degraded through hydrolysis, and the generated short-chain PFCA will continuously cycle along a degradation pathway similar to PFOA. During this process, Fe generated on the iron-based ceramic membrane... 2+ Oxidized to Fe by dissolved oxygen or ·OH 3+ This allows for the regeneration of the iron-based ceramic membrane. Furthermore, the iron-based ceramic membrane can also degrade PFOA and regenerate under simulated natural light. Although the efficiency is slightly lower compared to ultraviolet light, it still demonstrates promising application prospects.
Claims
1. A method for preparing a photo-regenerated iron-based ceramic membrane, characterized in that, Includes the following steps: (1) Grind the kaolinite and iron zeolite molecular sieve thoroughly to make them evenly mixed, and then add the binder and dispersion medium and continue grinding; (2) The mixture obtained in step (1) is dried at room temperature, and the dried powder is pressed into shape. (3) The material pressed in step (2) is sintered at high temperature, and the final iron-based ceramic film is obtained after sintering.
2. The method for preparing the photo-regenerated iron-based ceramic film according to claim 1, characterized in that, In step (1), the mass ratio of kaolinite to iron zeolite molecular sieve is 1:1 to 1:1.2, and the binder is a polyvinyl alcohol solution with a concentration of 5±0.5wt%. The mass of the added polyvinyl alcohol solution is 10±1wt% of the sum of the masses of kaolinite and iron zeolite molecular sieve.
3. The method for preparing the photo-regenerated iron-based ceramic film according to claim 1, characterized in that, In step (2), a hydraulic press is used for pressing and molding. The pressure of the hydraulic press is 150-200 MPa, and the holding time is 1-2 minutes.
4. The method for preparing the photo-regenerated iron-based ceramic film according to claim 1, characterized in that, In step (3), the preferred high-temperature sintering temperature is 900–1000℃, and the heating rate is 5–10℃ / min. -1 Sintering time: 2-2.5 hours.
5. A photo-regenerated iron-based ceramic membrane prepared by the method of preparing the photo-regenerated iron-based ceramic membrane according to claim 1.
6. The application of the photo-regenerated iron-based ceramic membrane according to claim 5 in the removal of PFOA.
7. The application according to claim 6, characterized in that, The iron-based ceramic membrane is used for filtering and removing low concentrations of PFOA from water.
8. The application according to claim 7, characterized in that, The iron-based ceramic membrane is fixed in a replaceable membrane filter and mounted on a syringe. Then, pressure is applied using the syringe to slowly filter the PFOA solution through the iron-based ceramic membrane.
9. The application of the photo-regenerated iron-based ceramic membrane according to claim 5 in the photodegradation of perfluorooctanoic acid.
10. The application according to claim 9, characterized in that, The iron-based ceramic film loaded with PFOA was irradiated with ultraviolet or white light at a power density of 35–40 mW / cm². -2 The reaction temperature is controlled at 25-30℃ for 12-24 hours.
